(untitled) (World Bulletin of Physical Education and Sports Science, 2025)
Chess is widely recognized not only as a competitive sport but also as a unique cognitive activity that integrates analytical reasoning, intuitive judgments and emotional self-regulation within a single decision-making environment. This study examines chess as a model of intellectual competition from a multidisciplinary perspective, focusing on the interaction between logical thinking, intuitive strategies and emotional regulation during competitive play. Drawing from concepts in cognitive psychology, sports pedagogy and neuroscience, the research highlights how chess players engage complex cognitive operations such as pattern recognition, situational analysis and predictive modelling while simultaneously managing stress, risk-taking and competitive pressure. The pedagogical relevance of chess is emphasized through its role in strengthening executive functions, improving long-term attention and enhancing metacognitive awareness among learners. In sports contexts, chess fosters resilience, self-control and strategic flexibility, which are critical for performance stability. The study also discusses the significance of training approaches that harmoniously develop both logical and intuitive components of thinking while integrating emotional intelligence skills. The findings aim to contribute to pedagogical practices in sports education systems, suggesting that chess can serve as an effective intellectual training tool for developing competitive competencies and psychological stability in students engaged in both physical and mental sports.